Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/jmri.21388
|View full text |Cite
|
Sign up to set email alerts
|

ADC value and diffusion tensor imaging of prostate cancer: Changes in carbon‐ion radiotherapy

Abstract: Purpose:To assess the apparent diffusion coefficient (ADC) value and diffusion tensor image (DTI) including fractional anisotropy (FA) of the noncancerous prostate and prostate cancer before and after carbon-ion radiotherapy (CIRT). Materials and Methods:Nine patients with biopsy-proven prostate cancer underwent 1.5T magnetic resonance (MR) examinations. One patient with benign prostatic hypertrophy and one healthy volunteer were also examined as references. The changes in ADC values and DTI of the entire pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 13 publications
9
37
0
4
Order By: Relevance
“…Our baseline, mean ADC values reflect this and are comparable to those established in the literature (34,35). When a cytotoxic response is induced, ADC values increase due to a lessening of diffusion restriction (36).…”
Section: Discussionsupporting
confidence: 89%
“…Our baseline, mean ADC values reflect this and are comparable to those established in the literature (34,35). When a cytotoxic response is induced, ADC values increase due to a lessening of diffusion restriction (36).…”
Section: Discussionsupporting
confidence: 89%
“…Lower ADC values are consistent with restricted water content in the extracellular space secondary to the dense cellularity of malignant tissue [21]. However, these differences may disappear after RT as ADC values may increase in the tumor region due to the radiation induced inflammatory swelling of tumour cells and decrease in the prostatic non-tumoral tissue due to stromal fibrosis possibly explaining the false positives or equivocal DWI studies in our series [22,23].…”
Section: Discussionsupporting
confidence: 67%
“…Thus, it can be inferred that the low and intermediate grades of PCa exhibit low aggression and the high grade of PCa may invade adjacent tissue. Takayama et al (20) observed that the fiber bundles of PCa were deformed but with no evident disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical Gleason scoring is performed in PCa specimens obtained by surgical resection or biopsy. Furthermore, the correlation between DTI and Gleason scores has been explored by measuring FA and ADC values, which may be beneficial in predicting the malignant degree of the tumor (20).…”
Section: Discussionmentioning
confidence: 99%